Implementation Of The Family Hope Program (PKH) In Alleviating Poverty In Sumedang Regency - Ajeng Nur Hanifah; Petrus Polyando; Dyah Poespita Ernawati (Sean Institute, 2024)
Poverty is one of the problems faced by developing countries in the world, including Indonesia. The government continues to strive to address the problem of poverty through various social policies or programs, one of which is the Family Hope Program (PKH) which is regulated in Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program. The research carried out was entitled